A Randomized, Multicenter, Double-Blind, Study to Evaluate the Safety and Efficacy of Estradiol Vaginal Cream 0.003% in Postmenopausal Women with Vaginal Dryness as the Most Bothersome Symptom - Archer, David F. (J Womens Health (Larchmt), 2018)
Background: Vulvovaginal atrophy (VVA) is characterized by vaginal/vulvar dryness, irritation, dyspareunia, or dysuria. The objective of this study was to examine the efficacy and safety of a very low-dose estradiol vaginal cream (0.003%) applied twice per week in postmenopausal women with VVA-related vaginal dryness. Materials and Methods: In this phase 3, randomized, double-blind, placebo-controlled, multicenter study, postmenopausal women with moderate–severe vaginal dryness as the most bothersome VVA symptom were randomized (1:1) to estradiol cream 0.003% (15 μg estradiol; 0.5 g cream) or placebo (0.5 g cream). Treatments were applied vaginally once daily for 2 weeks followed by two applications/week for 10 weeks. Coprimary outcomes were changes in severity of vaginal dryness, percentage of vaginal superficial and parabasal cells, and vaginal pH at final assessment. Additional outcomes comprised changes in severity of other VVA signs and symptoms. Adverse events (AEs) were assessed. Results: Of the 576 randomized participants, most were white and had an average age of 59 years. At final assessment, estradiol reduced vaginal dryness severity, decreased vaginal pH, increased superficial cell percentage, and decreased parabasal cell percentage versus placebo (p ≤ 0.05, all). Estradiol also reduced vaginal dryness severity at Weeks 4–12 and dyspareunia at Week 8 versus placebo (p ≤ 0.05, all). Improvements in vaginal/vulvar irritation/itching severity and dysuria were similar between estradiol and placebo. Estradiol had comparable rates of treatment-emergent AEs to placebo. No deaths occurred. Conclusions: Very low-dose estradiol vaginal cream (0.003%) dosed twice weekly is an effective and well-tolerated treatment for VVA symptoms and dryness associated with menopause.